Flooding of a carbonate platform: The Sian Kaʼan Wetlands, Yucatán, Mexico—A model for the formation and evolution of palustrine carbonate factories around the modern Caribbean Sea and in the depositional record. (14th February 2023) - Platt, Nigel H.; Wright, V. Paul
Abstract: The dynamic inter‐relationships between marine and freshwater carbonate depositional environments are illustrated in the Sian Ka'an Wetlands, a 5 280 km 2 complex of groundwater‐fed freshwater marshes, lakes and brackish coastal lagoons in the South‐East Yucatán Peninsula (Mexico). The Yucatán Platform was subaerially emergent and extensively karstified during the last glacial maximum at 18,  000 yr bp . The Late Holocene transgression has caused progressive reflooding of the continental margin, backstepping of the MesoAmerican Reef and encroachment of coastal environments into the platform interior as rising groundwaters flood an interconnected cave and sinkhole system and feed seasonal marshes above. The Sian Ka'an Wetlands form a vast palustrine carbonate factory which is directly juxtaposed and dynamically linked with the marine carbonate factory to seaward. Continuing sea‐level rise has caused synchronous landward migration of marginal marine and freshwater environments as beach barriers were breached and palustrine sloughs flooded to form marginal marine seagrass lagoons. The Rio Hondo Fault conditions fluid inflow while the sub‐environments of the Sian Ka'an Wetlands reflect tectonic controls on microtopography and hydroperiod. Modern analogues for the Sian Ka'an Wetlands include the Florida Everglades, formed during transgression of the Florida Platform, and relict marsh environments preserved on leeward shores of Andros, Abaco and other Bahama islands. A wide range of ancient examples deposited in coastal and continental interior settings similarly reflect seasonal aquifer rise in response to marine transgression and/or onlap of late‐stage basin fill onto a karstified pediment. Freshwater palustrine carbonate factories on carbonate platforms are transient deposystems, controlled by subtle water depth, climate, vegetation and hydrological factors while being critically sensitive to sea‐level changes and tectonics. The preservation potential of palustrine carbonates may be relatively low in coastal settings due to erosion or shallow marine overprinting, while greater further inland where marine flooding is rarer and in tectonically subsident continental interior basins where accommodation space is continuously created. Abstract : The Sian Ka'an Wetlands of SE Mexico form a vast freshwater carbonate factory located on the Yucatán Platform, directly juxtaposed with the shallow marine carbonate factory of the MesoAmerican Reef offshore. Following deep karstification during the late Pleistocene sea level low stand, Holocene transgression progressively flooded the Sian Ka'an Wetlands as aquifer rise has seen groundwaters emerge seasonally onto the platform top, while sea level rise has caused a landward migration of environments as palustrine sloughs have been flooded to form shallow marine seagrass lagoons in parallel with reef backstepping offshore. The Sian Ka'an Wetlands provide a model for modern palustrine carbonate environments around the Caribbean, as well as for ancient palustrine carbonates in transgressive coastal settings and within the late stage fill of inland continental interior basins, where aquifer rise through a karstified carbonate pediment sees the establishment of seasonal freshwater carbonate wetlands.